Driving productivity correspondence by using digital letter application / Dika Widyanti, Amaliyah and Rahmat Yuliawan - Widyanti, Dika; ., Amaliyah; Yuliawan, Rahmat (Universiti Teknologi MARA, Cawangan Melaka, 2022)
In the era of rapid technological developments, it can be easier to communicate with other parties. One of the communication media in printed form is letters. The research method uses descriptive qualitative. This qualitative descriptive study describes the procedures for using the E-letter application in correspondence activities at the Secretariat of the Sub Division of Program Preparation and Reporting of the Surabaya City Education Office (SCEO) through information and data analysis obtained. The procedure for using email applications can be divided into two: incoming mail and outgoing mail procedures. The process for entering the letter of SCEO can be through an incoming letter entry, or it can also be directly entered into the account belonging to the Secretary of SCEO. Secretariat Division of Program Preparation and Reporting Sub-Section uses e-Letter applications from the many outgoing letters that can be selected, usually used in only three categories of letters. The three categories of letters include invitation letters, notification/regular letters, and e-keynote speaker. The E-letter application, when logging in, requires a username and password. The username used is an Employee Identity Number which is only owned by Civil Servants. Meanwhile, in the Secretariat of the Sub-Division of Programming and Reporting, there are still staff who are not civil servants, so they have difficulty accessing the E-letter application. To overcome this problem, when logging in to the E-letter application, filling in the username, can use Employee Identification Number to make it easier for non-staff of Government to access the E-letter application. The correspondence productivity of digital mail are increasing content repository, reduced cost, improved efficiency, strengthening security, compliance and risk management, advanced customer service, and reducing carbon footprint.